2014
DOI: 10.1007/s10384-014-0354-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a visual aid using see-through display for patients with retinitis pigmentosa

Abstract: This device enabled the subjects to see objects that could not be recognized by the unaided eye. Our visual aid effectively assisted RP patients with night blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…It is estimated that 2.0 million individuals are affected with RP worldwide [ 1 ]. Although much effort has been made in developing new treatments, there is no effective treatment for RP [ 2 8 ]. Because RP is a progressive disease and can lead to severe visual impairments, it can lead to severe psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 2.0 million individuals are affected with RP worldwide [ 1 ]. Although much effort has been made in developing new treatments, there is no effective treatment for RP [ 2 8 ]. Because RP is a progressive disease and can lead to severe visual impairments, it can lead to severe psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Only 10 of the studies reviewed involved a quantitative assessment of mobility performance and of these, 8 of them [45][46][47][48][52][53][54]77 recorded a significant reduction in efficiency with vision enhancement. Of the other two studies, which observed similar or better efficiency, in both of them, 68,76 the mobility courses were relatively simple with large walkable areas and a small number of relatively large obstacles. Therefore, currently, there is no good evidence that vision enhancements using HMDs improve walking efficiency.…”
Section: Discussionmentioning
confidence: 77%
“… 54 Conversely, using four times minified black and white image overlays, another study observed a significant reduction in the number of collisions without a reduction in walking speed in eight people with PFL and night-blindness caused by RP compared to the performance without the HMD. 68 This study did not provide clinical information about the participants, and the apparent contradiction could result from differences in participants or differences in the complexity of the experimental environments.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations